If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3y+4(y+8)=-39
We move all terms to the left:
3y+4(y+8)-(-39)=0
We add all the numbers together, and all the variables
3y+4(y+8)+39=0
We multiply parentheses
3y+4y+32+39=0
We add all the numbers together, and all the variables
7y+71=0
We move all terms containing y to the left, all other terms to the right
7y=-71
y=-71/7
y=-10+1/7
| 83+26p=993 | | n=3n-7 | | 78x-39=12x+92 | | 64+128x=32x | | 4÷x-2=8÷x+5 | | 23+15c=-832 | | |3e|=15 | | 2(2+-3)=8(t+2) | | 2y=4-7(5) | | 20+8(q-8)=11 | | -4÷x-2=8÷x+5 | | |a|=6 | | 6.51/6.3+p=2.1 | | x2+20x+103=0 | | 36x-36x=204+15 | | 1+1/3y=1/4y | | -4x-2=8÷x+5 | | 13-a/11=7 | | 7(d-2)=5(d+2)12 | | t2+14t=49 | | 4r+6=2r=17 | | X×95=500+(x×45) | | 9=x/2+3 | | 0.4x-1.75=3.05 | | 7(d2)=5(d+2)12 | | 22-3y=9 | | 1/3x+2/5=1/5x-2/5 | | 0.6x+2.7=0.9x | | 6.3+p/3.1=2.1 | | 5–2s=3 | | 95=q-135 | | 3y-4=-7 |